Application of 1-(4-Cl-benzyl)-3-Cl- 4-(CF3-phenylamino)-1H-pyrrole-2,5-dione as a panspecific protein kinase inhibitor for inhibition of hematological complications in experimental chronic cholangitis in rats - Byelinska, I.V.; Kuznietsova, H.M.; Dziubenko, N.V.; Savych, Y.V.; Milokhov, D.S.; Khilya, O.V.; Rybalchenko, T.V. (Reports of the National Academy of Sciences of Ukraine, 2021)
The effect of a a panspecific inhibitor of pyrrole derivatives (1-(4-Cl-benzyl)-3-Cl-4-(CF3-phenylamino)-1Hpyrrole- 2,5-dione, MI-1), synthesized at the Kyiv National Taras Shevchenko University, on hematological manifestations of experimental α-anaphthyl isothiocyanate-induced chronic cholangitis is studied. It is found that MI-1 reduces the level of inflammation, which is confirmed by the normalization of the total number of leukocytes in blood due to a decrease in the number of eosinophilic and neutrophilic granulocytes and lymphocytes involved in the development of experimental chronic cholangitis. MI-1 restores the number of erythrocytes in blood through the activation of erythropoiesis, that is evident by an increase in the number of reticulocytes in blood of rats with experimental cholangitis. MI-1 normalizes the number of platelets in blood most likely due to inhibition of platelet formation in bone marrow, activated by the development of an inflammatory process in liver. MI-1 reduces the level of hematological complications of experimental chronic cholangitis in rats and with proven low overall and hematoxicity and hepatoprotective effect is promising for further research as a compound with anti-inflammatory activity.